Motivation on accounting choice of actuarial gain (loss) - Julio Hokky Sahputra; Taufik Hidayat (Journal of Economics, Business, and Accountancy Ventura, 2014)
This research aims to test whether there is any motivation from the management to choose their accounting policy in recognizing actuarial gain (loss) related to the defined benefit plan between corridor method and full recognition through OCI method based on IAS 19 (2004). Motivation theories in this research are asset pricing motivation, contracting motivation, and influencing external parties’ motivation. The research was done by using logit model and cross-section. The sample was taken from listed companies in 17 Europe’s Premier Indices from 2005 to 2012. The result shows that there are debt covenant motivation and these affect external parties motivation from management to recognize actuarial gain or loss. This result also shows that risk that affects management decision to switch from corridor method to full recognition through OCI method at which companies having high risk tend to avoid full recognitionthrough OCI method to prevent fluctuation on financial statements. This research conclusion confirms previous research that there are management motivations in selecting accounting method.